Insect haptoelectrical stimulation of Venus flytrap triggers exocytosis in gland cells - Scherzer, Sönke; Shabala, Lana; Hedrich, Benjamin; Fromm, Jörg; Bauer, Hubert; Munz, Eberhard; Jakob, Peter; Al-Rascheid, Khaled A. S.; Kreuzer, Ines; Becker, Dirk; Eiblmeier, Monika; Rennenberg, Heinz; et al. (National Academy of Sciences, 2017)
The Venus flytrap Dionaea muscipula captures insects and consumes their flesh. Prey contacting touch-sensitive hairs trigger traveling electrical waves. These action potentials (APs) cause rapid closure of the trap and activate secretory functions of glands, which cover its inner surface. Such prey-induced haptoelectric stimulation activates the touch hormone jasmonate (JA) signaling pathway, which initiates secretion of an acidic hydrolase mixture to decompose the victim and acquire the animal nutrients. Although postulated since Darwin’s pioneering studies, these secretory events have not been recorded so far. Using advanced analytical and imaging techniques, such as vibrating ion-selective electrodes, carbon fiber amperometry, and magnetic resonance imaging, we monitored stimulus-coupled glandular secretion into the flytrap. Trigger-hair bending or direct application of JA caused a quantal release of oxidizable material from gland cells monitored as distinct amperometric spikes. Spikes reminiscent of exocytotic events in secretory animal cells progressively increased in frequency, reaching steady state 1 d after stimulation. Our data indicate that trigger-hair mechanical stimulation evokes APs. Gland cells translate APs into touch-inducible JA signaling that promotes the formation of secretory vesicles. Early vesicles loaded with H⁺ and Cl⁻ fuse with the plasma membrane, hyperacidifying the “green stomach”-like digestive organ, whereas subsequent ones carry hydrolases and nutrient transporters, together with a glutathione redox moiety, which is likely to act as the major detected compound in amperometry. Hence, when glands perceive the haptoelectrical stimulation, secretory vesicles are tailored to be released in a sequence that optimizes digestion of the captured animal.